COMPONENT ANALYSIS OF THE DEVELOPMENTAL VECTOR OF URBAN AND DISTRICT SOCIOGEOSYSTEMS (ON EXAMPLE OF KHARKIV AND VOLYN REGIONS OF UKRAINE) - Ievgeniia Telebienieva; Taras Pogrebskyi (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2015)
The article deals with methodological questions about using component analysis to analyze the socio-economic development and the health care system development of urban and district sociogeosystems. It is proposed together with a common vector analysis to explore its projection on the axis of space – for the time-derivative of each process parameter in set of changes that makes it possible to study the development of sociogeosystem at the level of each parameter. Specific examples of using this method for the analysis of socio-economic development of the urban sociogeosystem of Kharkiv region and for analysis of health care system development of the district sociogeosystem of Volyn region are given.